PENINGKATAN PENYELESAIAN SOAL CERITA MATEMATIKA BERBANTUAN MEDIA PAPAN TEMPEL PADA PESERTA DIDIK KELAS I SEKOLAH DASAR - Rahmawati, Ratih Oktavia; Ambarwati, Esti; Habiby, Wahdan Najib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to improve the completion of mathematics story problems with the help of sticky boards in class I elementary school students. The type of research used in this research is Classroom Action Research (PTK). The analysis technique in this research uses qualitative and quantitative analysis. The research subjects were 28 class I students. Based on the results of the research and discussion, it showed that in the pre-cycle the students' completeness was 17.86%, then in the first cycle the students' completeness was 53.47%, there was an increase of 35.61%, and in cycle II, student completeness was 100%, there was an increase of 46.53%. Thus, there is an increase in solving mathematics story problems with the help of sticky boards in grade 1 elementary school students.